Computational electrochemistry study of derivatives of anthraquinone and phenanthraquinone analogues: the substitution effect. Issue 92 (20th September 2016) - Wang, Zhen; Li, Anyang; Gou, Lei; Ren, Jingzheng; Zhai, Gaohong
Abstract : Effects of functional group position on the calculated redox potential for the single electron-withdrawing group substitution of phenanthraquinone analogues. Abstract : The substituent effect on fused heteroaromatic anthraquinone and phenanthraquinone are investigated by density functional calculations to determine some guidelines for designing potential cathode materials for rechargeable Li-ion batteries. The calculated redox potentials of the quinone derivatives change monotonically with increasing number of substitutions. Full substitution with electron-withdrawing groups brings the highest redox potential; however, mono-substitution results in the largest mass energy density. Carbonyl groups are the most favorable active Li-binding sites; moreover, intramolecular lithium bonds can be formed between Li atoms and electronegative atoms from the substituent groups. The lithium bonds increase the redox potential by improving the thermodynamic stabilization of the lithiation derivatives. Furthermore, the calculation of nucleus-independent chemical shift indicates that the derivatives with Li-bound carbonyl groups are more stable than the bare derivatives.